2020
DOI: 10.1186/s12889-020-08464-4
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in smoking in Russia in the light of recent tobacco control measures: synthesis of evidence from multiple sources

Abstract: Background The study aims at identifying long-term trends and patterns of current smoking by age, gender, and education in Russia, including the most recent period from 2008 during which tobacco control policies were implemented, and to estimate the impact on mortality of any reductions in prevalence. We present an in-depth analysis based on an unprecedentedly large array of survey data. Methods We examined pooled micro-data on smoking from 17 roun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 24 publications
2
25
1
5
Order By: Relevance
“…The participation rate in KYH was 48%, although the educational profile as the participants was similar to that of the cities from which they came 15 . Moreover, the risk factor data is consistent with what previously observed, including smoking and blood pressure levels 41 , 42 . In the Tromsø Study the participation rate was 65% and risk factor prevalences we used from the Tromsø Study are comparable those from the HUNT Study in the county of Nord-Trøndelag, Norway 43 , 44 .…”
Section: Discussionsupporting
confidence: 91%
“…The participation rate in KYH was 48%, although the educational profile as the participants was similar to that of the cities from which they came 15 . Moreover, the risk factor data is consistent with what previously observed, including smoking and blood pressure levels 41 , 42 . In the Tromsø Study the participation rate was 65% and risk factor prevalences we used from the Tromsø Study are comparable those from the HUNT Study in the county of Nord-Trøndelag, Norway 43 , 44 .…”
Section: Discussionsupporting
confidence: 91%
“…This is surprising given historically very high smoking prevalence among Russian men. 7 Despite recent declines in smoking in Russia, 28 we did find here that the prevalence of current smoking and pack-year history was higher among the Russian than the Norwegian men. However, there was also a high prevalence of ex-smokers in the Norwegian sample therefore the current lung function damage in this sample could be attributable to higher levels of smoking in Norway in the past.…”
Section: Discussioncontrasting
confidence: 54%
“…For many years, about 60% of Russian men reported themselves as regular smokers, which was one of the highest male smoking rates in the world. Smoking prevalence is significantly lower among Russian women (10-12 percent), although the share of women who smoke increased from the mid-1990s until the mid-2000s, particularly among less-educated women (Shkolnikov et al 2020). Male smoking rates started declining around 2007 and, as of 2016, had fallen by more than 10 percentage points, a remarkable decline in smoking prevalence in less than a decade among a population whose smoking rate had not changed in several decades.…”
Section: Smoking Prevalence and Tobacco Control Policies In Russiamentioning
confidence: 99%
“…Tobacco control policies have received less attention in the literature, but these policies also have a significant impact on male mortality rates in Russia. Recent estimates indicate that smoking accounted for 26% of all male deaths in Russia in 2001 (and only 3% of female deaths; see Shkolnikov et al 2020). Denisova (2010), using individual-level panel data from the Russian Longitudinal Monitoring Survey for 1994-2007, found that the negative impact of smoking on longevity in Russia is comparable to the effect of alcohol consumption on longevity.…”
Section: The Role Of Government Policy In the Post-2005 Mortality Gainsmentioning
confidence: 99%